2022
DOI: 10.3389/fonc.2022.972383
|View full text |Cite
|
Sign up to set email alerts
|

CCL5 mediates breast cancer metastasis and prognosis through CCR5/Treg cells

Abstract: Background and aimsCCL5 is considered to contribute to the biological function of a variety of cancer types, but its specific mechanism is still unclear. This study aimed to reveal the mechanism of CCL5 in the invasion, metastasis, and prognosis of breast cancer.MethodsThe expression of CCL5 in tumor tissue and serum was measured with a Luminex protein detection kit, and the correlation between CCL5 and clinical parameters was evaluated. Kaplan–Meier analysis was used to analyze the effect of CCL5 on the progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…This suggests that increased CCL5 expression strengthens the defensive properties of the immune system. Qiu et al through their work showed that CCL5 can play an anti-tumor role in breast cancer [ 51 ]. CCL5/RANTES secretion was induced by IL-27 activity.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that increased CCL5 expression strengthens the defensive properties of the immune system. Qiu et al through their work showed that CCL5 can play an anti-tumor role in breast cancer [ 51 ]. CCL5/RANTES secretion was induced by IL-27 activity.…”
Section: Discussionmentioning
confidence: 99%
“…HSPA8 is a new biomarker related to prognosis and immune infiltration in TNBC ( Ying et al, 2022 ). CCL5 mediates breast tumor progression and recurrence by interacting with the CCR3 axis ( Yamaguchi et al, 2021 ), recruiting macrophages ( Walens et al, 2019 ) and regulating the CD4 + /CD8 + , CCR5 + /CD4 + or Treg/CCR5 + cell ratios ( Qiu et al, 2022 ). IFI16-dependent STING pathway can potentiate HER2 breast cancer responses to immunotherapy ( Ong et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated therapeutic value in regulating anoikis and pyroptosis. By interacting with chemokine receptor type 5 (CCR5), CCL5 could promote breast cancer progression and metastasis via Treg cells (45). Release of IL-18 is reported to initiate pyroptosis in breast cancer, facilitating tumor metastasis (46-48).…”
Section: Discussionmentioning
confidence: 99%